Mirror neurons and their role in communication - Shete, Anjali N.; Garkal, K. D. (International Journal of Research in Medical Sciences, 2017)
Actions done by others are probably the most important stimuli of our lives. Most of others’ actions do not convey intentional information to the observer. From them, however, we understand what others are doing and we can infer why they are doing it. This involuntary communication is fundamental for interpersonal relations, and is at the basis of social life. What is the mechanism underlying our capacity to understand others’ actions? The traditional view is that actions done by others are understood in the same way as other visual stimuli. Thus, action understanding is based on the visual analysis of the different elements that form an action. For example, when we observe a girl picking up a flower, the analyzed elements would be her hand, the flower, and the movement of the hand towards the flower. The association of these elements and inferences about their interaction enables the observer to understand the witnessed action. The discovery of neurons that code selectively biological motion has better specified the neural basis of this recognition mechanism. These theoretical considerations received strong support from the discovery that in the motor cortex of the macaque monkey there is a particular set of neurons that discharge both when the monkey observes a given motor act and when it does the same act. These neurons called “mirror neurons,” represent a system that directly matches observed and executed actions.